The role of Tagalog in ESL writing clues from students think-aloud protocols - Castro, Carolyn D. (2004)
To explore the role of the LI in L2 writing, 30 first-year college students were taped as they thought aloud while writing an essay in English. The tapes were transcribed and analysed, and a total of 615 composing behaviors were verbalized in their L1, Tagalog. The eight composing behaviors that were verbalized most frequently in Tagalog were text evaluation (25%), brainstorming (23%), lexical insertion and substitution (20%), idea evaluation (17%), organizing/deciding (5%), self-instruction (4%), metacomments (4%), and idea elicitation (2%). Results showed that the L1 facilitated planning and revising processes, and enabled the postponement of low-level writing goals so L2 writers can attend to higher level writing goals. Writing teachers need to reassess the role of the L1 in the L2 writing classroom, and explore the potential benefits that may be reaped when L2 learners tap their L1 as they plan, retrieve, generate, organize, evaluate, and revise their written products.
Includes bibliographical references (pages 38-39).